Pengaruh Keyakinan Epistemologi dan Efikasi Diri terhadap Kecemasan dalam Menulis Jurnal Ilmiah: Analisa Structural Equation Modelling : [The Influence of Epistemological Beliefs and Self-Efficacy on Anxiety in Writing Scientific Journals: Structural Equation Modeling Analysis] - Andrea Halim; Geraldine Maria T. Supit; I Made Samuel Raharja; Sukma Ramadhan (Jurnal Teropong Pendidikan, 2023)
In an academic setting, students are often required to write scientific journals as part of their curriculum. However, a common phenomenon is the anxiety experienced by most students when writing scientific journals. To understand the dynamics behind this, the purpose of this study was to focus on two main variables: Epistemological Beliefs and Self-Efficacy, as well as how these two variables affect Anxiety in writing scientific journals. Data was collected from 54 students of Universitas Pelita Harapan batches 49 and 50 through a specially designed questionnaire. After the data was collected, the Structural Equation Modelling-Partial Least Square analysis was carried out with the help of SmartPLS software to understand the relationship between variables. The results of the analysis confirmed that Epistemological Beliefs do have a positive influence on students' Self-Efficacy. Furthermore, both variables, Epistemological Beliefs and Self-Efficacy, showed a negative influence on Anxiety in writing scientific journals. Therefore, it is concluded that this finding provides important insights for educators and educational institutions about the importance of strengthening students' Epistemological Beliefs and Self-Efficacy to ensure they are more confident and reduce anxiety in writing scientific journals.